Innovation Package and Scaling Readiness assessment for restoring rangelands: the art of flexible livestock grazing to restore soil health, ecosystem function and ecosystem services in Tunisia - Rudiger, Udo (International Center for Agricultural Research in the Dry Areas, 2024)
This report presents a generated analysis of the outputs resulting from the implementation of the Scaling Readiness methodology in the context of rangeland restoration (termed Gdel) in Tunisia. Gdel's approach pertains to the practice of flexible livestock grazing. In this method, rangeland resting periods are meticulously and collectively scheduled to facilitate the restoration of soil health, ecosystem function, and ecosystem services within the Tunisian landscape. The report delineates the sociotechnical interventions that are requisite to accompany the Gdel in order to ensure its optimal success and scalability.